DOI: 10.14264/uql.2018.276
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Comparison of Energy Generation Technologies in Remote Australia

Abstract: Increased implementation of renewable technology for power generation is critical to achieving the emissions targets set by many countries, as well as delivering an economically viable method of providing power to isolated communities. This project set out to analyse and compare three technologies, namely Solar PV, Concentrating Solar Thermal with thermal storage and diesel generators, for deployment in remote Australian areas. In this paper, a detailed literature review of past projects involving renewable en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…This is a key result, as it shows that even with excellent solar resources, there are strong merits to hybridisation with a diesel generator. These results corroborate the work of Swanson (2017), and indicate that despite differences in methodology and assumptions, the overall results observed are quite similar. Hence it may be posited that the results obtained here will extend well to tests under a different load profile, and with different CST configurations.…”
Section: Optimal Hybrid System Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This is a key result, as it shows that even with excellent solar resources, there are strong merits to hybridisation with a diesel generator. These results corroborate the work of Swanson (2017), and indicate that despite differences in methodology and assumptions, the overall results observed are quite similar. Hence it may be posited that the results obtained here will extend well to tests under a different load profile, and with different CST configurations.…”
Section: Optimal Hybrid System Resultssupporting
confidence: 88%
“…Based on these results, it is clear that the storage fill time, which controls the ratio of field capacity to storage capacity, plays a key role in reducing excess production and costs, and hence is an important consideration. This is a key result, as in a previous analysis by Swanson (2017) the fill time was treated as a constant to simplify the optimisation. This analysis has revealed that there are strong merits to including the fill time as an optimisation parameter, as it is directly linked to the excess production.…”
Section: Optimal Hybrid System Resultsmentioning
confidence: 92%
See 1 more Smart Citation